Hypopigmented macules of the limbs in two sisters: report on familial Bier spots - Giuseppe Stinco; Enzo Errichetti; Pasquale Patrone (Sociedade Brasileira de Dermatologia, 2015)
AbstractBier spots are asymptomatic, small, irregular, hypopigmented macules characterized by a normal histological appearance, which are usually found on the arms and legs of young adults. We describe the simultaneous presence of Bier spots in two siblings. This finding is unusual since, to the best of our knowledge, concurrent familial cases have never been reported in the literature.